Recent Research on Croatian Witchcraft Trials - Vedriš, Trpimir (2006)
Paper presents recent research on witchcraft trials in Civil Croatia, Slavonia, Istria and Dalmatia in the Early Modern Period (ca. 1400-1760). Author presents new source material and discusses authors and research conducted in Croatia after 1990.